Formulation, Characterization, and Evaluation of Topical Anti-inflammatory Herbal Gel: Formulation, Characterization, and Evaluation of Topical Anti-inflammatory Herbal Gel - Bhalke, Dr. Rasika D. (International Journal of Pharmaceutical & Biological Archive, 2019)
The aim of the present investigation was to prepare and evaluate topical gel containing capsaicinoid and/or aqueous extract of Tridax procumbens L. (AETP) leaves and/or aqueous extract of Ocimum sanctum leaves. First gel base was prepared using various different concentrations of Carbopol-934, propylene glycol 400, methylparaben, and propylparaben and required amount of distilled water. The optimized base was selected for the incorporation of capsaicinoid and AETP. Then, skin pH (6.8–7) was maintained by dropwise addition of triethanolamine. Prepared formulations were evaluated for physical appearance, pH, spreadability, viscosity, and homogeneity. Prepared formulations have proceeded for skin irritation on the animal model (rabbit). All gels were evaluated for anti-inflammatory activity using carrageenan-induced rat paw edema model on Albino Wistar rats of either sex (150–200 g). Change in edema volume of the rat hind paw was measured, and percent inhibition was calculated. Stability studies have meted out as per the ICH guidelines for 3 months at different temperatures and humidity. Results reveal that all formulations have shown good appearance, homogeneity, and spreadability. The viscosity of all formulations is ranging between 3500 and 5000 centipoises. All formulations have shown no skin irritation, i.e., erythema and edema to animals. Formulations F1, F2, and F3 have shown significant (P<0.001) anti-inflammatory activity and shown significant inhibition of the inflammation to the extent of 42.37%, 55.93%, and 45.76% at 3 h and 68%, 69.33%, and 54.67% at 4 h, respectively, while the reference drug; diclofenac sodium reduced the inflammation by 59.32% at 3 h and 74.67% at 4 h.